Production of transgalactosylated oligosaccharides (TOS) by galactosyltransferase activity from Penicillium simplicissimum - Cruz, R.; Cruz, V. D.; Belote, J. G.; Khenayfes, M. D.; Dorta, C.; Oliveira, L H D; Ardiles, E.; Galli, A. (Elsevier B.V., 1999)
Ingestion of transgalactosylated oligosaccharides (TOS) and other non-digestible oligosaccharides (NDOs) induces a significant increase in Bifidobacterium, Lactobacillus and some desirable species of Streptococcus populations in the gut of human and other animals (prebiotic effect). This change in the intestinal flora is responsible for several beneficial physiological effects such as a decrease of putrefactive products in the feces, lower blood cholesterol content, higher Ca2+ absorption, a smaller loss of bone tissue in ovariotomized female rats and a lower incidence of colon cancer. beta-Galactosidase from Penicillium simplicissimum, a strain isolated from soil, showed high galactosyltransferase activity when incubated with a highly concentrated lactose solution. Optimum pH and temperature ranges for hydrolytic activity were 4.0-4.6 and 55-60 degrees C, respectively, for a lactose concentration of 5.0% (w/v). Maximal galactosyltransferase activity was obtained at pH 6.5 and 50 degrees C and TOS synthesis was positively associated with lactose concentration in the reaction medium. Thus, when 50 ml of a 60% (w/v) lactose solution was incubated with 26.6 U of beta-galactosidase under the best pH and temperature conditions for transferase activity, a final product with 30.5% TOS (183 mg ml(-1)), 27.5% residual lactose and 42.0% monosaccharides was obtained. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: galactooligosaccharides; Penicillium simplicissimum; galactosyltransferase; prebiotic effect; transgalactosylation; functional foods